MODAL SOSIAL DALAM MITIGASI STRUKTURAL BANJIR: STUDI KASUS FORUM PENGURANGAN RISIKO BENCANA DI DAS KALIJOMPO - Gymnastiar Tira Wicaksana; Joko Mulyono; Jati Arifiyanti (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Disasters are events that endanger and disrupt community life. Mitigation is an effort to reduce disaster risk through structural and non-structural approaches. Jember Regency, East Java, has a fairly high potential for flood disasters, especially in the Kalijompo watershed area. The Kalijompo Disaster Risk Reduction Forum (F-PRB Kapo) is a disaster-aware community that plays a role in flood management in the region. The multidimensional characteristics of flood disasters encompassing infrastructure, policy, and natural resource management require a collaborative approach from various stakeholders. The research entitled